TINGKAT STRES MAHASISWA FAKULTAS KESEHATAN ANGKATAN 2021 PADA MASA PANDEMI COVID-19 - Widigdya, Aquamarine; Sari, Annisa Putri Komala; Ardana, Berliana Deswita; Lestari, Dian Nila; Meilani, Oktaviana Dewi; P.M, Satria Devanda (Universitas Duta Bangsa Surakarta, 2024)
On March 11, 2020, the World Health Organization (WHO) declared the Coronavirus Disease 2019 (Covid-19) a global pandemic. The government provides a policy of limiting activities outside the home, so school activities are suspended. Several studies have shown that this change in teaching and learning habits creates obstacles that will trigger stress in students. New students have their own stress load, such as adjusting to the environment and lecture activities.To describe the stress level of students in the 2021 batch of learning activities at the Faculty of Health Sciences, Duta Bangsa University during the Covid-19 Pandemic. This study used an observational-descriptive method with a cross sectional approach. The data used is primary data, taken from the Indonesian version of the Medical Student Stressor Questionnaire (MSSQ). The research population is the entire batch of 2021 with a total sampling technique of sampling. This study found the results that the majority of students experienced moderate stress as many as 45 people (54.22%), 15 people mild stress (18.07%), 22 people stressed (26.51%) and very stressed 1 person. (1.20%). In this study, most of the 2021 students of the Faculty of Health Sciences, Duta Bangsa University experienced moderate stress.